PENGARUH KUALITAS PELAYANAN TERHADAP LOYALITAS PELANGGAN MELALUI KEPUASAN PELANGGAN DI GRAND GARDEN RESTAURANT BOGOR - Rahmat Hidayat (Lembaga Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Pariwisata Bogor, 2021)
This study aims to determine how the effect of service quality on customer loyalty and to determine the effect of service quality on customer loyalty mediated by customer satisfaction at Grand Garden Restaurant Bogor. The research method used is a quantitative approach with descriptive analysis methods, data collection techniques are carried out by distributing questionnaires to 149 respondents in the research object and hypothesis testing methods using path analysis. The results of hypothesis testing show that service quality has a significant effect on customer loyalty, this is indicated by the coefficient value obtained, namely 0.159. The results of the second hypothesis test show that service quality has an influence on customer loyalty mediated by customer satisfaction, the significance value of customer satisfaction is greater than service quality with a coefficient value of 0.243. From the hypothesis test, it can be concluded that customer satisfaction has an indirect effect on increasing customer loyalty.